Tax-incentivized housing production and the affordability crisis: International lessons from the low-income housing tax credit program in the United States - Wijburg, Gertjan (Housing studies, 2024)
Historically, many Western nations have subsidized public and affordable housing with public grants and government-backed loans. However, in response to declining housing affordability and high land and development costs, various national governments are now introducing tax-based housing incentives to promote affordable housing production by private actors. Understanding the broader implications of this shift to tax subsidy and private investment, this review reflects on the market outcomes of arguably the most documented tax-based housing program in the Western world: the low-income housing tax credit program (LIHTC) in the United States. Although LIHTC remains a unique and distinctive instrument, some valuable lessons can be learned from it. In comparative terms, the program offers stricter affordability requirements than its counterparts introduced in countries like Australia, Chile, Colombia, France and Germany. Furthermore, it is accompanied by stronger regulations to commit investors and developers to the housing cause on a more long-term basis. However, despite potential benefits, tax-incentivized housing production does not necessarily result in efficient or equitable housing solutions. In non-American contexts, its increased importance coincides with the emergence of market-oriented social welfare systems where affordable rents are set higher and where tenure is more flexible and heterogeneous.